Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Gravity Digital Printing - Evi Vanda Amijanti; Bangun Putra Prasetya (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the effect of compensation and work environment on employee productivity at Gravity Digital Printing. In the face of increasingly fierce competition, it is important for companies to understand the factors that can increase employee productivity. This research uses a qualitative approach with an interview method with seven employees at Gravity Digital Printing. The results showed that fair and competitive compensation can improve employee motivation and performance. In addition, a conducive, comfortable, and supportive work environment also plays an important role in increasing employee productivity. Although some aspects of the work environment need improvement, such as facilities and room comfort, overall, a positive work environment is able to support employee performance. These findings confirm the importance of Gravity Digital Printing to continuously evaluate compensation policies and improve work environment conditions to ensure sustainable employee well-being and productivity. The results of this study are expected to serve as a foundation for companies in formulating effective strategies and policies to improve employee performance and achieve organizational goals.